Communicative approach and the production of narrative texts in 6th grade students of IE n° 21575. Barranca. Lima - Huaman Collao , Liliana (2023)
The current research work is to determine the relationship between sixth grade students' communicative approach and the production of narrative texts. This work used a quantitative method, an observational-non-experimental, descriptive, correlational cross-sectional design. For the purposes of this study, the relationship between two variables was analyzed in the process of learning narrative texts. The sample consists of 30 students enrolled in 2019. As a research instrument, questionnaires were used to assess communicative approaches, and titles were used to assess the production of narrative texts. The obtained data were evaluated and processed and statistically analyzed using the statistical program SPSS v 25. Finally, it is concluded that there is a significant correlation between communication style and narrative text creation. According to Spearman's rho test, the correlation coefficient is 0.9, which indicates that communication style has a good influence on narrative text focus management. Students present narrative texts better in class.